Vulnerabilidad, pobreza y políticas sociales : abanico de sentidos en América Latina, Europa y China (CLACSO, 2020)
Vulnerability, poverty and social policies seem to be three intertwined concepts in the notion of lack or scarcity and are often used, on many occasions, as a synonym, although from their definitions they are not. So what do they have in common? Between distances and proximities, convergences and analytical and disciplinary divergences, this book aims to discuss/analyze the ways of defining and intervening in vulnerability, poverty and social policies from a critical look in key of some components of social sensitivities that they intersect with the processes of social structuring from Argentina, Colombia, Mexico, China, Spain, France, Ireland and Italy.